Pengembangan Keterampilan Sosial dan Akademik Siswa Melalui Strategi Pembelajaran Kooperatif - M. Irfan Saputra; Muhammad Irsyad Al Faiz; Gusmaneli Gusmaneli (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
This study aims to explore the effectiveness of cooperative learning strategies in developing students' social and academic skills in high schools in Padang City. Cooperative learning involves students working in small groups to achieve specific learning goals. The main characteristics of this strategy include direct face-to-face interaction, individual and group accountability, cooperation, social skills development, and group evaluation. The implementation of techniques such as Jigsaw, Think-Pair-Share, Group Investigation, and STAD shows significant improvements in students' social and academic skills. The study results indicate that cooperative learning not only enhances academic understanding but also enriches students' interpersonal skills, which are crucial for character and competence development in the future.